2019
DOI: 10.1093/infdis/jiz046
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Cross-Protection Against Subsequent Febrile Respiratory Illness Episodes From Prior Infections by Different Viruses Among Singapore Military Recruits 2009–2014

Abstract: Background Few studies have evaluated the relative cross-protection conferred by infection with different groups of viruses through studies of sequential infections in humans. We investigated the presence of short-lived relative cross-protection conferred by specific prior viral infections against subsequent febrile respiratory illness (FRI). Methods Men enlisted in basic military training between December 2009 and December 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 27 publications
2
11
0
1
Order By: Relevance
“…Similarly, immune cells and club cells that survived an initial IAV infection nonspecifically mediated protection against an influenza B virus challenge through alterations in the composition of cellular infiltration and inflammatory cytokine profiles; it is possible cells in the lung following the initial RSV infection in this study were similarly primed to protect against the secondary influenza virus challenge (52). Consistent with results in mice, infection with influenza virus or adenovirus has been documented to provide protection against subsequent febrile respiratory illnesses in humans (53). Thus, it is possible that memory T cells and innate immune responses may have contributed nonspecifically to the TRM-mediated protection against IAV infection observed in this study.…”
Section: Discussionsupporting
confidence: 76%
“…Similarly, immune cells and club cells that survived an initial IAV infection nonspecifically mediated protection against an influenza B virus challenge through alterations in the composition of cellular infiltration and inflammatory cytokine profiles; it is possible cells in the lung following the initial RSV infection in this study were similarly primed to protect against the secondary influenza virus challenge (52). Consistent with results in mice, infection with influenza virus or adenovirus has been documented to provide protection against subsequent febrile respiratory illnesses in humans (53). Thus, it is possible that memory T cells and innate immune responses may have contributed nonspecifically to the TRM-mediated protection against IAV infection observed in this study.…”
Section: Discussionsupporting
confidence: 76%
“…These observations in 1918 also are supported by more recent examples. Among military recruits in Singapore in 2009–2013, prior adenovirus or influenza virus infection conferred cross-protection against subsequent febrile illness episodes relative to prior infection due to other circulating viruses [34].…”
Section: Discussionmentioning
confidence: 99%
“…NK cells are also key mediators of cross-protection whereby they expand during the initial infection and are primed to undergo a second expansion as well as produce more cytokines upon a secondary infection ( 207 ). More recently, a Singapore study of military recruits within a 5-year period showed that men infected with influenza were protected against subsequent infection with adenovirus ( 79 ). It should be noted, however, that cross-protection between infections is generally considered to be dependent on both non-specific reprogramming of innate immunity as well as activation of memory T cells.…”
Section: Toll-like Receptor Agonist-mediated Trained Immunity and Promentioning
confidence: 99%